Correlation between genetic architecture of Fe and Zn accumulation and yield components in common bean (Phaseolus vulgaris L.) - Diaz Bolivar, Wilson Santiago; Polania Perdomo, Jose Arnulfo; Ariza-Suárez, Daniel; Cajiao V., César Hernando; Grajales Bedoya, Miguel Angel; Raatz, Bodo; Beebe, Stephen E. (2021)
These datasets contain phenotypic and genotypic data of three biparental Mesoamerican biofortified populations of common bean (SCR16 x SMC40, SMC44 x SCR9 and SMC33 x SCR16). The main goal of these populations is to be used for genetic analysis and applications in breeding and breeding tool development, as well as information for basic research questions aiming to uncover the genetic basis of correlation between Fe/Zn accumulation and yield components. The raw data phenotypic data come from trials carried out in Palmira (Colombia). These trials were laid out in the field with an augmented design with three blocks using 5 different check lines (SER118, SER16, TIO CANELA 75, SEN56 and DOR390) and each parent for each population in 2011, 2012, 2013, 2014 and 2015. Seven traits were evaluated: Fe accumulation (SdFe), Zn accumulation (SdZn), Pod harvest index (PHI), Seed number (SdN), Pod number (PdN), 100 seed weight (100SdW) and Seeds per pod (Sd/Pd). The agronomic performance of the population was modeled using linear mixed models. The genotypic datasets include a variant call format (VCF) file from each one of the three populations